Growth of nototheniid fish, Trematomus bernacchii and Pagothenia borchgrevinki reared in aquarium - Sakakibara, Shigeru; Kondo, Yoshiaki; Tobayama, Teruo; Hoshiai, Takao (National Institute of Polar Research, 1989)
P(論文) Antarctic nototheniid fish, Trematomus bernacchii and Pagothenia borchgrevinki were reared in the aquarium at the Kamogawa Sea World, Japan. Two T. bernacchii and 4 P. borchgrevinki individuals survived for about 2000 days in good condition. Growth in the body length and body weight of both species was observed. One individual of T. bernacchii spawned once a year since 1984. During about 1 month before spawning the fish stopped feeding. The similar behavior in feeding was observed in the other individual of T. bernacchii. departmental bulletin paper